Silica-alumina sol cross-linked silica nanofiber aerogel and method of making same

CN118666563BActive Publication Date: 2026-10-23新疆理工学院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410755320.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-11
Publication Date
2026-10-23
Estimated Expiration
2044-06-11

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供一种硅铝溶胶交联的二氧化硅纳米纤维气凝胶及其制备方法,以解决现有技术中二氧化硅纳米纤维气凝胶抗高温烧结性能差的问题

Benefits of technology

[0021](1)相较于有机硅烷偶联剂作为交联剂,本发明采用无机硅铝溶胶作为交联剂制备的硅铝溶胶交联的二氧化硅纳米纤维气凝胶,提高了二氧化硅纳米纤维气凝胶的耐高温性能,同时抑制了氧化铝在高温条件下发生相变。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118666563B_ABST
    Figure CN118666563B_ABST
Patent Text Reader

Abstract

The application provides a kind of silica nanofiber aerogel crosslinked with silica-alumina sol and a preparation method thereof, and belongs to the technical field of high-temperature-resistant thermal insulation materials.The application first hydrolyzes aluminum salt to obtain aluminum hydroxide sol, mixes silicon source, anhydrous ethanol, hydrochloric acid and water, and then hydrolyzes to obtain silica sol, then mixes the aluminum hydroxide sol and the silica sol to obtain silica-alumina sol, and finally mixes silica nanofiber, silica-alumina sol and tert-butyl alcohol to obtain a nanodispersion, which is sequentially subjected to first freeze-drying and second freeze-drying to obtain silica nanofiber aerogel crosslinked with silica-alumina sol.The silica nanofiber aerogel crosslinked with silica-alumina sol prepared by the application inhibits the phase transition of aluminum oxide under high-temperature conditions, and improves the high-temperature resistance of the silica nanofiber aerogel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-temperature resistant thermal insulation materials, and in particular to a silica nanofiber aerogel crosslinked with aluminosilicate sol and its preparation method. Background Technology

[0002] With the development of nanofiber aerogels, due to their excellent thermal insulation properties, they can be used as super thermal insulation materials in a variety of fields and are currently the solid materials with the best thermal insulation performance.

[0003] Currently, silica nanofiber aerogel composites are widely researched and applied. However, traditional silica nanofiber aerogels are prone to high-temperature sintering, while alumina, although a high-performance, heat-resistant material, undergoes a phase transition at high temperatures. Therefore, researching a silica-alumina sol-crosslinked silica nanofiber aerogel and its preparation method to improve its resistance to high-temperature sintering is of great significance. Summary of the Invention

[0004] The purpose of this invention is to provide a silica nanofiber aerogel crosslinked with aluminosilicate and its preparation method, so as to solve the problem of poor high-temperature sintering resistance of silica nanofiber aerogel in the prior art.

[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0006] This invention provides a method for preparing silica nanofiber aerogel crosslinked with aluminosilicate sol, comprising the following steps:

[0007] (1) The aluminum salt was hydrolyzed to obtain aluminum hydroxide sol;

[0008] (2) The silicon source, anhydrous ethanol, hydrochloric acid and water were mixed and hydrolyzed to obtain silica sol;

[0009] (3) Mix aluminum hydroxide sol and silica sol to obtain silica-alumina sol;

[0010] (4) Mix silica nanofibers, silica-alumina sol and tert-butanol, and then freeze-dry the resulting nano-dispersion in sequence to obtain silica nanofiber aerogel crosslinked with silica-alumina sol.

[0011] Preferably, in step (1), aluminum salt and water are mixed during aluminum salt hydrolysis, wherein the mass ratio of aluminum salt to water is 5-10:13-17; the aluminum salt includes one or more of aluminum nitrate, aluminum chloride, aluminum sulfate and aluminum isopropoxide; and the temperature of aluminum salt hydrolysis is 75-85°C.

[0012] Preferably, in step (2), the mass ratio of silicon source, anhydrous ethanol, hydrochloric acid and water is 1-1.5:3-7:0.2-1.0:80-120; the hydrolysis temperature is 75-85℃ and the hydrolysis time is 20-40 min.

[0013] Preferably, in step (2), the silicon source comprises one or more of methyl orthosilicate, ethyl orthosilicate, methyltrimethoxysilane, trimethylchlorosilane, hexamethyldisilazane, and silicon tetrachloride; and the hydrochloric acid has a mass percentage concentration of 0.5-1.5%.

[0014] Preferably, in step (3), the mass ratio of aluminum hydroxide sol to silica sol is 1-10:1000; and the mixing time is 1-3 hours.

[0015] Preferably, the mass ratio of aluminum hydroxide sol in step (3) to silica nanofibers in step (4) is 1:1 to 10.

[0016] Preferably, in step (4), the mass ratio of silica nanofibers to tert-butanol is 1:0 to 20.

[0017] Preferably, in step (4), the temperature of the first freeze-drying is -25 to -15°C, and the time of the first freeze-drying is 6 to 14 hours.

[0018] Preferably, in step (4), the temperature of the second freeze-drying is -80 to -60°C, and the time of the second freeze-drying is 70 to 200 hours.

[0019] The present invention also provides a silica nanofiber aerogel crosslinked with silica-alumina sol prepared by the above-described preparation method.

[0020] The beneficial effects of this invention are:

[0021] (1) Compared with organosilane coupling agents as crosslinking agents, the silica nanofiber aerogel prepared by inorganic silica alumina sol as crosslinking agent in this invention improves the high temperature resistance of silica nanofiber aerogel and inhibits the phase transformation of alumina under high temperature conditions.

[0022] (2) The silica nanofiber aerogel crosslinked by silica-alumina sol prepared by the present invention has excellent compression resilience, and after calcination at 1200℃ and compression test, the collapse rate is only 3.3%. Attached Figure Description

[0023] Figure 1 The images show the actual product of the silica nanofiber aerogel crosslinked with silica-alumina sol prepared in Example 1, where a is a top view and b is a front view.

[0024] Figure 2 The images show the actual products of the silica nanofiber aerogel crosslinked with silica-alumina sol obtained in Example 1 after calcination at different temperatures, where a is calcined at 30℃, b is calcined at 300℃, c is calcined at 500℃, d is calcined at 800℃, e is calcined at 1000℃, and f is calcined at 1200℃.

[0025] Figure 3 The graph shows the compressive strain of the silica nanofiber aerogel crosslinked with silica-alumina sol after calcination at 300°C in Example 1.

[0026] Figure 4 The graph shows the compressive strain of the silica nanofiber aerogel crosslinked with silica-alumina sol after calcination at 500°C in Example 1.

[0027] Figure 5 The graph shows the compressive strain of the silica nanofiber aerogel crosslinked with silica-alumina sol after calcination at 800℃ in Example 1.

[0028] Figure 6 The graph shows the compressive strain of the silica nanofiber aerogel crosslinked with silica-alumina sol after calcination at 1000℃ in Example 1.

[0029] Figure 7 The graph shows the compressive strain of the silica nanofiber aerogel crosslinked with silica-alumina sol after calcination at 1200℃ in Example 1.

[0030] Figure 8 The image shows the elasticity test curves of the silica nanofiber aerogel crosslinked with silica-alumina sol obtained in Example 1, with a compressive strain of 60% and 50 cycles. In the image, a is the stress-strain curve and b is the stress-time curve.

[0031] Figure 9 The graphs show the hydrophilicity and hydrophobicity test results of the silica nanofiber aerogel crosslinked with silica-alumina sol obtained in Example 1, where a represents the moment when the water droplet just falls and b represents the process of water droplet absorption.

[0032] Figure 10 The graphs show the thermal insulation performance of the silica nanofiber aerogel crosslinked with silica-alumina sol and the multilayer aluminum foil paper prepared in Example 1. The first row shows the silica nanofiber aerogel crosslinked with silica-alumina sol, and the second row shows the multilayer aluminum foil paper.

[0033] Figure 11 This is a scanning electron microscope image of the silica nanofiber aerogel crosslinked with silica-alumina sol obtained in Example 1.

[0034] Figure 12This is a comparison chart of the fracture strength test results of the silica nanofiber aerogel crosslinked with silica-alumina sol in Example 1, the silica nanofiber aerogel in Comparative Example 1, and the zirconia / silica nanofiber aerogel in Comparative Example 2. In the chart, 1 represents the fracture strength of the silica nanofiber aerogel in Comparative Example 1, 2 represents the fracture strength of the zirconia / silica nanofiber aerogel, and 3 to 6 represent the fracture strength of different samples of the silica nanofiber aerogel crosslinked with silica-alumina sol obtained in Example 1.

[0035] Figure 13 The infrared spectra of the silica nanofiber aerogel crosslinked with silica-alumina sol in Example 1 and the silica nanofiber aerogel in Comparative Example 1 are shown. Detailed Implementation

[0036] This invention provides a method for preparing silica nanofiber aerogel crosslinked with aluminosilicate sol, comprising the following steps:

[0037] (1) The aluminum salt was hydrolyzed to obtain aluminum hydroxide sol;

[0038] (2) The silicon source, anhydrous ethanol, hydrochloric acid and water were mixed and hydrolyzed to obtain silica sol;

[0039] (3) Mix aluminum hydroxide sol and silica sol to obtain silica-alumina sol;

[0040] (4) Mix silica nanofibers, silica-alumina sol and tert-butanol, and then freeze-dry the resulting nano-dispersion in sequence to obtain silica nanofiber aerogel crosslinked with silica-alumina sol.

[0041] In this invention, during the hydrolysis of aluminum salt, it is preferable to mix aluminum salt and water, wherein the mass ratio of aluminum salt to water is 5-10:13-17, preferably 6-9:14-16, and more preferably 7-9:14-15; the aluminum salt comprises one or more of aluminum nitrate, aluminum chloride, aluminum sulfate and aluminum isopropoxide, preferably one or more of aluminum nitrate, aluminum chloride and aluminum isopropoxide, and more preferably aluminum nitrate and aluminum isopropoxide.

[0042] In this invention, when the aluminum salt is aluminum nitrate and aluminum isopropoxide, the mass ratio of aluminum nitrate to aluminum isopropoxide is 3.5-3.9:5.0-5.2, preferably 3.6-3.8:5.05-5.15, and more preferably 3.7-3.8:5.1.

[0043] In this invention, the temperature for hydrolyzing the aluminum salt is 75-85°C, preferably 78-82°C, and more preferably 80°C; the hydrolysis is carried out under stirring conditions until it becomes clear and transparent.

[0044] In this invention, in step (2), the mass ratio of silicon source, anhydrous ethanol, hydrochloric acid and water is 1-1.5:3-7:0.2-1.0:80-120, preferably 1.1-1.4:4-6:0.6-0.9:90-110, and more preferably 1.2-1.3:5:0.7-0.8:100; the hydrolysis temperature is 75-85℃, preferably 78-82℃, and more preferably 80℃; the hydrolysis time is 20-40 min, preferably 25-35 min, and more preferably 30 min.

[0045] In this invention, in step (2), the silicon source comprises one or more of methyl orthosilicate, tetraethyl orthosilicate, methyltrimethoxysilane, trimethylchlorosilane, hexamethyldisilazane, and silicon tetrachloride, preferably one or more of methyl orthosilicate, tetraethyl orthosilicate, methyltrimethoxysilane, and trimethylchlorosilane, more preferably methyl orthosilicate or tetraethyl orthosilicate; the mass percentage concentration of the hydrochloric acid is 0.5-1.5%, preferably 0.8-1.2%, more preferably 1.0%.

[0046] In this invention, in step (3), the mass ratio of aluminum hydroxide sol to silica sol is 1 to 10:1000, preferably 1.5 to 8:1000, and more preferably 2 to 5:1000.

[0047] In this invention, in step (3), when mixing aluminum hydroxide sol and silica sol, it is preferable to add aluminum hydroxide sol dropwise into silica sol, and the mixing time is 1 to 3 hours, preferably 1.5 to 2.5 hours, and more preferably 2 hours.

[0048] In this invention, the mass ratio of aluminum hydroxide sol in step (3) to silica nanofibers in step (4) is 1:1 to 10, preferably 1:3 to 7, and more preferably 1:4 to 6.

[0049] In this invention, there is no particular limitation on the specific source of the silica nanofibers; any silica nanofibers that meet the requirements of this application and are obtained by means known in the art are acceptable.

[0050] The silica nanofibers used in the embodiments of the present invention are preferably prepared by the following method: a silicon source, anhydrous ethanol, hydrochloric acid and water are mixed and hydrolyzed, and the resulting silica gel is electrospun to obtain silica nanofibers.

[0051] In this invention, during the preparation of the silica nanofibers, the mass ratio of silicon source, anhydrous ethanol, hydrochloric acid, and water is 16–20:6–10:1.0–1.5:2–3, preferably 17–19:7–9:1.1–1.4:2.4–2.8, wherein the mass percentage concentration of hydrochloric acid is 0.5–1.5%, preferably 0.8–1.2%, and more preferably 1%; the hydrolysis temperature is 75–85°C, preferably 78–82°C, and more preferably... The temperature is 80℃, and the hydrolysis time is 40-80 min, preferably 50-70 min, and more preferably 60 min; the electrospinning parameters are: voltage 15-22 kV, preferably 18-21 kV, and more preferably 20 kV; spinning temperature 20-30℃, preferably 23-28℃, and more preferably 25℃; the distance between the electrospinning nozzle and the receiving device is 13-20 cm, preferably 14-18 cm, and more preferably 15 cm.

[0052] In this invention, in step (4), the mass ratio of silica nanofibers to tert-butanol is 1:0 to 20, preferably 1:5 to 15, and more preferably 1:8 to 12.

[0053] In this invention, silica nanofibers, silica-alumina sol and tert-butanol are mixed and then preferably stirred at high speed, wherein the stirring speed is 1500-2500 rpm, preferably 1800-2200 rpm, more preferably 2000 rpm, and the stirring time is 40-80 min, preferably 50-70 min, more preferably 60 min.

[0054] In this invention, in step (4), the temperature of the first freeze-drying is -25 to -15°C, preferably -23 to -17°C, and more preferably -21 to -19°C; the time of the first freeze-drying is 6 to 14 hours, preferably 8 to 12 hours, and more preferably 10 hours.

[0055] In this invention, in step (4), the temperature of the second freeze-drying is -80 to -60°C, preferably -75 to -65°C, and more preferably -70°C. The time of the second freeze-drying is 70 to 200 hours, preferably 72 to 180 hours, and more preferably 108 to 168 hours.

[0056] The present invention also provides a silica nanofiber aerogel crosslinked with silica-alumina sol prepared by the above-described preparation method.

[0057] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0058] The preparation process of silica nanofibers used in this embodiment of the invention is as follows: 18.8g of tetraethyl orthosilicate, 7.91g of anhydrous ethanol, 1.27g of hydrochloric acid (mass percentage concentration of 1%) and 2.68g of deionized water are mixed and heated to 80℃ for 60min to hydrolyze and obtain silica gel. Then, silica nanofibers are prepared by electrospinning. The process parameters are: voltage of 20kV, spinning temperature of 25℃, and distance between the electrospinning nozzle and the receiving device of 15cm.

[0059] Example 1

[0060] Add 3.75g of aluminum nitrate to 14g of deionized water and stir at room temperature for 30 minutes. Then add 5.10g of aluminum isopropoxide and continue stirring at room temperature until dissolved. Then heat to 80℃ and hydrolyze under stirring until it becomes clear and transparent, obtaining aluminum hydroxide sol. Mix 6.71g of tetraethyl orthosilicate, 26.85g of anhydrous ethanol, 3.76g of hydrochloric acid (1% by mass) and 483g of deionized water, heat to 80℃ and hydrolyze for 30 minutes to obtain silica sol, and cool to room temperature.

[0061] 1.1 g of aluminum hydroxide sol was slowly added dropwise to 515.35 g of silica sol, and stirred at room temperature for 2 h to obtain a silica-alumina sol. 5.37 g of silica nanofibers were cut into small pieces and added to the silica-alumina sol, followed by 55.40 g of tert-butanol. The mixture was placed in a high-speed stirrer and stirred at 2000 rpm for 1 h to obtain a nanofiber dispersion. This dispersion was poured into a crystallizing dish with a diameter of 125 mm and a height of 65 mm, and then freeze-dried at -21 °C for 12 h. The mixture was then transferred to a freeze dryer and freeze-dried at -70 °C for 168 h to obtain a silica nanofiber aerogel (diameter 118 mm, height 40 mm) crosslinked with a silica-alumina sol.

[0062] The density of the silica nanofiber aerogel crosslinked with the above-mentioned aluminosilicate sol was determined to be 0.0135 g / cm³. 3 The porosity is 97.9%.

[0063] Six silica nanofiber aerogels crosslinked with aluminosilicate sol were prepared according to the above method, and then calcined at different temperatures: 30℃, 300℃, 500℃, 800℃, 1000℃, and 1200℃. After being raised to the above temperatures, they were held at those temperatures for 30 minutes. The physical images of the calcined silica nanofiber aerogels crosslinked with aluminosilicate sol are shown below. Figure 2 As shown, from Figure 2 It can be seen that after calcination at different temperatures, the macroscopic morphology of the silica nanofiber aerogel crosslinked with aluminosilicate sol did not collapse or shrink.

[0064] Compression tests were conducted on the silica nanofiber aerogels crosslinked with aluminosilicate sol after calcination at 300℃, 500℃, 800℃, 1000℃, and 1200℃. Each sample was subjected to compressive strains of 20%, 40%, and 60% sequentially. The results are as follows: Figures 3-7 As shown, Figure 3 The silica nanofiber aerogel, which is a cross-linked silica-alumina sol treated with calcination at 300℃, has a collapse rate of only 3.5% after being compressed again under different compressive strains. Figure 4 The silica nanofiber aerogel, which is a cross-linked silica-alumina sol treated with calcination at 500℃, has a collapse rate of only 3.3% after being compressed again under different compressive strains. Figure 5 The silica nanofiber aerogel, which is cross-linked with silica-alumina sol after calcination at 800℃, has a collapse rate of only 3% after being compressed again with different compressive strains. Figure 6 The silica nanofiber aerogel, which was calcined at 1000℃ and crosslinked with aluminosilicate sol, showed a collapse rate of only 3.3% after being compressed again under different compressive strains; from Figure 7 It can be seen that the silica nanofiber aerogel crosslinked with silica-alumina sol after calcination at 1200℃ has a collapse rate of only 3.3% after being compressed again under different compressive strains. This indicates that the silica nanofiber aerogel crosslinked with silica-alumina sol has good high-temperature resistance.

[0065] The silica nanofiber aerogel crosslinked with silica-alumina sol prepared in Example 1 was subjected to cyclic compression tests with a compressive strain of 60%. After 50 cycles of compression tests, its stress-strain curves and stress-time curves are shown below. Figure 8 As shown, when the silica nanofiber aerogel crosslinked with aluminosilicate sol is subjected to cyclic compression at a compressive strain of 60%, the closed-loop shape of the cyclic curves basically overlaps, indicating excellent fatigue resistance. After completing the cyclic compression performance test, the maximum compressive stress hardly decreases significantly, which fully demonstrates that the silica nanofiber aerogel crosslinked with aluminosilicate sol has excellent compression resilience.

[0066] The hydrophilicity / hydrophobicity of the silica nanofiber aerogel crosslinked with silica-alumina sol prepared in Example 1 was tested, and the results are as follows: Figure 9 As shown, where Figure 9 In Figure a, the water droplet is just falling, and in Figure b, the water droplet is being absorbed. The test results show that it only takes 0.06 seconds from the moment the water droplet falls onto the surface of the silica nanofiber aerogel crosslinked with aluminosilicate to the moment the water droplet is absorbed, indicating that the silica nanofiber aerogel crosslinked with aluminosilicate has superhydrophilicity.

[0067] The thermal insulation performance of the silica nanofiber aerogel crosslinked with silica-alumina sol prepared in Example 1 was tested: two freshly picked dandelion flowers were placed on top of the silica nanofiber aerogel crosslinked with silica-alumina sol and on top of a multilayer aluminum foil, respectively, and then burned over an alcohol lamp. The thermal insulation performance test process is as follows. Figure 10 As shown, where Figure 10 The first row shows the changes in a dandelion flower placed on a silica nanofiber aerogel crosslinked with aluminosilicate sol. As the flame continued to burn, the outer petals began to wither after 3 minutes. Figure 10 The second line shows the changes in the dandelion flower placed on multiple layers of aluminum foil: as the flame continued to burn, the bottom of the dandelion flower charred after 40 seconds of burning, and the entire dandelion flower charred after 75 seconds of burning. This indicates that the silica nanofiber aerogel crosslinked with silica-alumina sol in Example 1 has good thermal insulation properties.

[0068] Figure 11 The image shows a scanning electron microscope (SEM) image of the silica nanofiber aerogel crosslinked with silica-alumina sol obtained in Example 1. It can be seen that the surface of the silica nanofibers has agglomerated particles, which indicates that the silica-alumina sol is loaded on the surface of the silica nanofibers.

[0069] Example 2

[0070] Add 3.75g of aluminum nitrate to 14g of deionized water and stir at room temperature for 30 minutes. Then add 5.10g of aluminum isopropoxide and continue stirring at room temperature until dissolved. Heat to 80℃ and hydrolyze under stirring until it becomes clear and transparent, obtaining aluminum hydroxide sol. Mix 0.87g of tetraethyl orthosilicate, 3.5g of anhydrous ethanol, 0.49g of hydrochloric acid (1% by mass) and 70g of deionized water, heat to 80℃ and hydrolyze for 30 minutes to obtain silica sol, then cool to room temperature.

[0071] 0.1 g of aluminum hydroxide sol was slowly added dropwise to 65 g of silica sol, and stirred at room temperature for 2 h to obtain a silica-alumina sol. 0.7 g of silica nanofibers were chopped and added to the silica-alumina sol, followed by 10.03 g of tert-butanol. The mixture was then stirred at 1500 rpm for 80 min in a high-speed stirrer to obtain a nanofiber dispersion. This dispersion was poured into a mold with a diameter of 55 mm and a height of 40 mm, placed in a refrigerator, and freeze-dried at -25 °C for 6 h. It was then transferred to a freeze dryer and freeze-dried at -80 °C for 72 h to obtain a silica nanofiber aerogel (53 mm in diameter and 35 mm in height) crosslinked with a silica-alumina sol.

[0072] Example 3

[0073] Add 3.75g of aluminum nitrate to 14g of deionized water and stir at room temperature for 30 minutes. Then add 5.10g of aluminum isopropoxide and continue stirring at room temperature until dissolved. Heat to 80℃ and hydrolyze under stirring until clear and transparent, obtaining aluminum hydroxide sol. Mix 6.53g of tetraethyl orthosilicate, 25.01g of anhydrous ethanol, 3.65g of hydrochloric acid (1% by mass), and 500g of deionized water, and heat to 80℃ for 30 minutes to hydrolyze, obtaining silica sol. Cool to room temperature.

[0074] 1.01 g of aluminum hydroxide sol was slowly added dropwise to 475 g of silica sol, and stirred at room temperature for 2 h to obtain a silica-alumina sol. 5.22 g of silica nanofibers were chopped and added to the silica-alumina sol, followed by 52.11 g of tert-butanol. The mixture was placed in a high-speed stirrer and stirred at 2500 rpm for 40 min to obtain a nanofiber dispersion. This dispersion was poured into a crystallizing dish with a diameter of 125 mm and a height of 65 mm, and then freeze-dried at -15 °C for 12 h. The resulting product was then transferred to a freeze dryer and freeze-dried at -60 °C for 168 h to obtain a silica nanofiber aerogel (diameter 118 mm, height 35 mm) crosslinked with a silica-alumina sol.

[0075] Comparative Example 1

[0076] Weigh 2.50g of tetraethyl orthosilicate, 10g of anhydrous ethanol, 200g of deionized water, and 1.40g of 1% hydrochloric acid. Use a magnetic stirrer to stir and hydrolyze at 80℃ for half an hour to obtain a silica sol. Weigh 2g of silica nanofibers, cut them into small pieces, and put them into the silica sol. Add 20g of tert-butanol and stir at 2000rpm for 1 hour to obtain a fiber dispersion. Pour the dispersion into a mold with a diameter of 55mm and a height of 60mm, place it in a refrigerator, and freeze-dry at -25℃ for 7 hours. Then transfer it to a freeze dryer and freeze-dry at -80℃ for 72 hours to obtain a silica nanofiber aerogel with a diameter of 53mm and a thickness of 55mm.

[0077] Comparative Example 2

[0078] First, weigh 1.25g of tetraethyl orthosilicate, 5g of anhydrous ethanol, 100g of deionized water, and 0.7g of 1% hydrochloric acid. Use a magnetic stirrer to stir and hydrolyze at 80℃ for half an hour to obtain a silica sol. Add 0.5g of zirconium oxychloride solution (11% by mass) and continue stirring for 10 minutes to obtain a zirconium silica sol. Weigh 1g of silica nanofibers, cut them into small pieces, and put them into the zirconium silica sol. Add 10g of tert-butanol and stir at 2000rpm for 1 hour to obtain a fiber dispersion. Pour the dispersion into a mold with a diameter of 55mm and a height of 40mm, place it in a refrigerator, and freeze-dry at -25℃ for 7 hours. Then transfer it to a freeze dryer and freeze-dry at -80℃ for 72 hours to obtain a zirconium oxide / silica nanofiber aerogel with a diameter of 53mm and a thickness of 35mm.

[0079] The tensile strength of the silica nanofiber aerogel crosslinked with silica-alumina sol in Example 1, the silica nanofiber aerogel in Comparative Example 1, and the zirconia / silica nanofiber aerogel in Comparative Example 2 was tested. The test method was as follows: the thickness and width of the sample were measured, the cross-sectional area was calculated, and a universal tensile testing machine was used to perform the tensile test at a tensile rate of 200 mm / min at room temperature. The maximum force at fracture was recorded, and the tensile strength was obtained by dividing the maximum force by the cross-sectional area. The results are as follows. Figure 12 As shown, the tensile strength of the silica nanofiber aerogel in Comparative Example 1 was 0.011 MPa, and the tensile strength of the zirconia / silica nanofiber aerogel in Comparative Example 2 was 0.013 MPa. The tensile strengths of the four samples prepared according to the preparation method of Example 1 were 0.017 MPa, 0.0173 MPa, 0.021 MPa, and 0.023 MPa, respectively, which are 1.5 to 2.3 times that of the silica nanofiber aerogel and 1.3 to 1.77 times that of the zirconia / silica nanofiber aerogel.

[0080] Infrared spectroscopy analysis was performed on the silica nanofiber aerogel crosslinked with silica-alumina sol in Example 1 and the silica nanofiber aerogel in Comparative Example 1. The results are as follows: Figure 13 As shown: in the range of 4000-400cm -1 Within the range, 3398cm -1 The nearby absorption peak is caused by the stretching vibration of hydroxyl groups in the bound water on the sample surface, at 1591 cm⁻¹. -1 The nearby peak corresponds to the stretching vibration peak of the CO bond, at 1336 cm⁻¹. -1 Nearby is the vibrational peak of hydroxide ions in aluminum hydroxide, at 1072 cm⁻¹. -1 The absorption peak corresponds to the stretching vibration of the Al-O-Si bond, at 1046 cm⁻¹. -1The nearby high absorption peak is attributed to the asymmetric tensile vibration of Si-O-Si, 936 cm⁻¹. -1 The bending vibration of the CO bond at a nearby location, 791 cm -1 The absorption peak near 444 cm⁻¹ is caused by the asymmetry of the Si-O-Si bonds. -1 The peaks in the vicinity increase significantly from a to b, which is the result of the superposition of Si-O and Al-O bonds.

[0081] As shown in the above embodiments, this invention provides a silica nanofiber aerogel crosslinked with aluminosilicate sol and its preparation method. First, aluminum salt is hydrolyzed to obtain aluminum hydroxide sol. Then, a silicon source, anhydrous ethanol, hydrochloric acid, and water are mixed and hydrolyzed to obtain a silica sol. Next, the aluminum hydroxide sol and the silica sol are mixed to obtain a silica alumina sol. Finally, silica nanofibers, the silica alumina sol, and tert-butanol are mixed, and the resulting nano-dispersion is sequentially subjected to a first freeze-drying and a second freeze-drying to obtain the silica nanofiber aerogel crosslinked with aluminosilicate sol. The silica nanofiber aerogel crosslinked with aluminosilicate sol prepared by this invention inhibits the phase transition of alumina under high-temperature conditions and improves the high-temperature resistance of the silica nanofiber aerogel.

[0082] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing silica nanofiber aerogel crosslinked with aluminosilicate sol, characterized in that, Includes the following steps: (1) The aluminum salt was hydrolyzed to obtain aluminum hydroxide sol; (2) The silicon source, anhydrous ethanol, hydrochloric acid and water were mixed and hydrolyzed to obtain silica sol; (3) Mix aluminum hydroxide sol and silica sol to obtain silica-alumina sol; (4) Mix silica nanofibers, silica-alumina sol and tert-butanol, and then freeze-dry the resulting nano-dispersion in sequence to obtain silica nanofiber aerogel crosslinked with silica-alumina sol. In step (3), the mass ratio of aluminum hydroxide sol to silica sol is 1~10:1000; The mass ratio of aluminum hydroxide sol in step (3) to silica nanofibers in step (4) is 1:1~10.

2. The preparation method according to claim 1, characterized in that, In step (1), aluminum salt and water are mixed during aluminum salt hydrolysis, wherein the mass ratio of aluminum salt to water is 5~10:13~17; the aluminum salt includes one or more of aluminum nitrate, aluminum chloride, aluminum sulfate and aluminum isopropoxide; the temperature of aluminum salt hydrolysis is 75~85℃.

3. The preparation method according to claim 1 or 2, characterized in that, In step (2), the mass ratio of silicon source, anhydrous ethanol, hydrochloric acid and water is 1~1.5:3~7:0.2~1.0:80~120; the hydrolysis temperature is 75~85℃ and the hydrolysis time is 20~40min.

4. The preparation method according to claim 3, characterized in that, In step (2), the silicon source includes one or more of methyl orthosilicate, ethyl orthosilicate, methyltrimethoxysilane, trimethylchlorosilane, hexamethyldisilazane, and silicon tetrachloride; the mass percentage concentration of the hydrochloric acid is 0.5-1.5%.

5. The preparation method according to claim 1, 2, or 4, characterized in that, In step (3), the mixing time is 1 to 3 hours.

6. The preparation method according to claim 5, characterized in that, In step (4), the mass ratio of silica nanofibers to tert-butanol is 1:0~20.

7. The preparation method according to claim 4 or 6, characterized in that, In step (4), the temperature of the first freeze-drying is -25~-15℃, and the time of the first freeze-drying is 6~14h.

8. The preparation method according to claim 7, characterized in that, In step (4), the temperature of the second freeze-drying is -80~-60℃, and the time of the second freeze-drying is 70~200h.

9. The silica nanofiber aerogel crosslinked with aluminosilicate sol prepared by any one of claims 1 to 8.